Keupayaan membran Ferum (III)-Kitosan sebagai elektrod pemilihan ion ferum(III). - Abu Hasan, Zalena (1995)
The heterogenous Fe(III)-chitosan membranes have shown linear Nernst respone towards Soluble Fe3+ in the concerntration range of 5 x 10-6 to 1x10 -3.